The value of information to foraging Calliope Hummingbirds. Issue 2 (2nd April 2016) - Ward, David
Abstract : Foragers may vary in their memories regarding the location and expected quality of resources. This difference in memory often corresponds to whether a forager either simultaneously encounters or sequentially encounters its food. To test for the effects of information, I examined the foraging patterns of calliope hummingbirds consuming different concentrations of sucrose that were marked or unmarked. I also examined the effects of uncertainty associated with alternative food sources by altering the mean and variance in sucrose concentration in marked and unmarked feeders. I found that hummingbirds feeding from marked feeders were more selective when Rich (= high sucrose items) and Poor (= low sucrose items) resources occurred in distinct, pure patches as opposed to patches containing a mixture of Rich and Poor items. When resource types were intermixed, hummingbirds feeding on marked feeders were selective as a continuous function, and foragers feeding on unmarked feeders were selective as a nonlinear function, of the relative values of different resources. Only one prediction of foraging on marked feeders was not supported, namely when Poor-quality items were located near Rich items, calliope hummingbirds did not show a greater preference for Poor items than when Poor items were far from Rich items. This last-mentioned result may indicate that the travel distance between Rich and Poor items was too short to warrant differentiating between Rich and Poor feeders. Hummingbirds preferred marked feeders when the mean sucrose concentration was greater or equal to that of unmarked feeders, but preferred unmarked feeders when mean sucrose concentration was lower in marked feeders. There was a significant positive correlation between visits to marked feeders and the coefficient of variation of unmarked feeders. These results indicate that when all things are equal, calliope hummingbirds prefer to forage where most information is available about resource quality.